Amfetamin in metamfetamin: mehanizem delovanja, učinki, zastrupitev in diagnostika - Ostrovršnik, Jaka (Medicinski razgledi, 2011)
Amphetamine consumption is highly spread throughout the world, especially in the Unites States of America, Australia and Asia. In Slovenia, the consumption of amphetamines and methamphetamines is not so spread and, furthermore, it is also not increasing. Amphetamines cause a euphoric state. Their effects are an immediate consequence of an increased release of dopamine, serotonin and noradrenaline in synapses of the central nervous system. Amphetamines are classified as substances that share an amphetamine skeleton. Amphetamines differ in their pharmacokinetic properties (absorption,distribution, metabolism and excretion) and potency, and some amphetamines also have a specific mechanism of action. Amphetamine usage is dangerous as can result in potentially lethal acute poisoning because of sympathomimetic overstimulation of the cardiovascular system. The first choice for the treatment of poisoning would be benzodiazepines, which suppress the nervous system. A prolonged, chronic usage of amphetamines, particularly methamphetamine, is neurotoxic and produces distinctive neurocognitive disorders. Despite being dangerous, amphetamines are used to treat attention deficit hyperactivity disorder and narcolepsy. This type of treatment is not registered in the European Union, however, because of its potential for the development of addiction. Unfortunately, there is no effective pharmacotherapy for the treatment of amphetamine addiction, but studies about the usage of the atypical antipsychotic and calcium channel blocker is radipine and the antiepileptic drug vigabatrin show promising results for future treatment.
Keywords: amfetamin; metamfetamin; farmakologija; nevrotoksičnost; zdravljenje odvisnosti; učinki